Multisystem mitochondrial diseases due to mutations in mtDNA-encoded subunits of complex I - Danhelovska, Tereza; Kolarova, Hana; Zeman, Jiri; Hansikova, Hana; Vaneckova, Manuela; Lambert, Lukas; Kucerova-Vidrova, Vendula; Berankova, Kamila; Honzik, Tomas; Tesarova, Marketa (BMC pediatrics, 2020)
BACKGROUND: Maternally inherited complex I deficiencies due to mutations in MT-ND genes represent a heterogeneous group of multisystem mitochondrial disorders (MD) with a unfavourable prognosis. The aim of the study was to characterize the impact of the mutations in MT-ND genes, including the novel m.13091 T > C variant, on the course of the disease, and to analyse the activities of respiratory chain complexes, the amount of protein subunits, and the mitochondrial energy-generating system (MEGS) in available muscle biopsies and cultivated fibroblasts. METHODS: The respiratory chain complex activities were measured by spectrophotometry, MEGS were analysed using radiolabelled substrates, and protein amount by SDS-PAGE or BN-PAGE in muscle or fibroblasts. RESULTS: In our cohort of 106 unrelated families carrying different mtDNA mutations, we found heteroplasmic mutations in the genes MT-ND1, MT-ND3, and MT-ND5, including the novel variant m.13091 T > C, in 13 patients with MD from 12 families. First symptoms developed between early childhood and adolescence and progressed to multisystem disease with a phenotype of Leigh or MELAS syndromes. MRI revealed bilateral symmetrical involvement of deep grey matter typical of Leigh syndrome in 6 children, cortical/white matter stroke-like lesions suggesting MELAS syndrome in 3 patients, and a combination of cortico-subcortical lesions and grey matter involvement in 4 patients. MEGS indicated mitochondrial disturbances in all available muscle samples, as well as a significantly decreased oxidation of [1-14C] pyruvate in fibroblasts. Spectrophotometric analyses revealed a low activity of complex I and/or complex I + III in all muscle samples except one, but the activities in fibroblasts were mostly normal. No correlation was found between complex I activities and mtDNA mutation load, but higher levels of heteroplasmy were generally found in more severely affected patients. CONCLUSIONS: Maternally inherited complex I deficiencies were found in 11% of families with mitochondrial diseases in our region. Six patients manifested with Leigh, three with MELAS. The remaining four patients presented with an overlap between these two syndromes. MEGS, especially the oxidation of [1-14C] pyruvate in fibroblasts might serve as a sensitive indicator of functional impairment due to MT-ND mutations. Early onset of the disease and higher level of mtDNA heteroplasmy were associated with a worse prognosis.
Keywords: mitochondriální DNA; respirační komplex I; DNA, Mitochondrial; Mitochondria; MELAS syndrome; fibroblasty; mutace; Mitochondrial Diseases; Fibroblasts; magnetická rezonanční tomografie; Age of Onset; Adolescent; Brain; Infant; mitochondriální nemoci; Child; MEGS; věk při počátku nemoci; dítě; Adult; biopsie; Muscle, Skeletal; dospělí; Leighova nemoc; mladiství; kosterní svaly; mtDNA; novorozenec; kultivované buňky; syndrom MELAS; Leigh Disease; lidé; ženské pohlaví; MT-ND genes; Humans; MELAS Syndrome; Infant, Newborn; kojenec; mozek; Electron Transport Complex I; Leigh syndrome; Biopsy; Cells, Cultured; Mutation; Magnetic Resonance Imaging; Female; Complex I